Genotypic Resistance of Pyrazinamide but Not Minimum Inhibitory Concentration Is Associated With Longer Time to Sputum Culture Conversion in Patients With Multidrug-resistant Tuberculosis - Kuhlin, Johanna; Davies Forsman, Lina; Mansjö, Mikael; Jonsson Nordvall, Michaela; Wijkander, Maria; Wagrell, Charlotta; Jonsson, Jerker; Groenheit, Ramona; Werngren, Jim; Schön, Thomas; Bruchfeld, Judith (Clinical infectious diseases, 2021)
Pyrazinamide (PZA) resistance in multidrug-resistant tuberculosis (MDR-TB) is common; yet, it is not clear how it affects interim and treatment outcomes. Although rarely performed, phenotypic drug susceptibility testing (pDST) is used to define PZA resistance, but genotypic DST (gDST) and minimum inhibitory concentration (MIC) could be beneficial. We aimed to assess the impact of PZA gDST and MIC on time to sputum culture conversion (SCC) and treatment outcome in patients with MDR-TB.BACKGROUNDPyrazinamide (PZA) resistance in multidrug-resistant tuberculosis (MDR-TB) is common; yet, it is not clear how it affects interim and treatment outcomes. Although rarely performed, phenotypic drug susceptibility testing (pDST) is used to define PZA resistance, but genotypic DST (gDST) and minimum inhibitory concentration (MIC) could be beneficial. We aimed to assess the impact of PZA gDST and MIC on time to sputum culture conversion (SCC) and treatment outcome in patients with MDR-TB.Clinical, microbiological, and treatment data were collected in this cohort study for all patients diagnosed with MDR-TB in Sweden from 1992-2014. MIC, pDST, and whole-genome sequencing of the pncA, rpsA, and panD genes were used to define PZA resistance. A Cox regression model was used for statistical analyses.METHODSClinical, microbiological, and treatment data were collected in this cohort study for all patients diagnosed with MDR-TB in Sweden from 1992-2014. MIC, pDST, and whole-genome sequencing of the pncA, rpsA, and panD genes were used to define PZA resistance. A Cox regression model was used for statistical analyses.Of 157 patients with MDR-TB, 56.1% (n = 88) had PZA-resistant strains and 49.7% (n = 78) were treated with PZA. In crude and adjusted analysis (hazard ratio [HR], 0.49; 95% conficence interval [CI], .29-.82; P = .007), PZA gDST resistance was associated with a 29-day longer time to SCC. A 2-fold decrease in dilutions of PZA MIC for PZA-susceptible strains showed no association with SCC in crude or adjusted analyses (HR, 0.98; 95% CI, .73-1.31; P = .89). MIC and gDST for PZA were not associated with treatment outcome.RESULTSOf 157 patients with MDR-TB, 56.1% (n = 88) had PZA-resistant strains and 49.7% (n = 78) were treated with PZA. In crude and adjusted analysis (hazard ratio [HR], 0.49; 95% conficence interval [CI], .29-.82; P = .007), PZA gDST resistance was associated with a 29-day longer time to SCC. A 2-fold decrease in dilutions of PZA MIC for PZA-susceptible strains showed no association with SCC in crude or adjusted analyses (HR, 0.98; 95% CI, .73-1.31; P = .89). MIC and gDST for PZA were not associated with treatment outcome.In patients with MDR-TB, gDST PZA resistance was associated with a longer time to SCC. Rapid PZA gDST is important to identify patients who may benefit from PZA treatment.CONCLUSIONSIn patients with MDR-TB, gDST PZA resistance was associated with a longer time to SCC. Rapid PZA gDST is important to identify patients who may benefit from PZA treatment.